2009
DOI: 10.1038/hdy.2009.158
|View full text |Cite
|
Sign up to set email alerts
|

Range shifts of Potentilla fruticosa on the Qinghai-Tibetan Plateau during glacial and interglacial periods revealed by chloroplast DNA sequence variation

Abstract: The Qinghai-Tibetan Plateau is one of the most extensive habitats for alpine plants in the world. Therefore, the patterns of genetic variation in populations on the Plateau can reveal the detailed demographic history of alpine plants. We analysed the geographical structure of chloroplast matK sequence variation in Potentilla fruticosa L. (Rosaceae), a shrub currently found across the entire Plateau. We obtained sequence data from 508 individuals from 23 populations at sites ranging from the high-altitude inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
37
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 38 publications
5
37
2
Order By: Relevance
“…In an alternative scenario, plants in the QTP show high genetic diversity and ancestral haplotypes, which suggest an in situ survival during the LGM on the plateau [13], [18]. Nevertheless, our study reveals a distinct phylogeographical history of plants occurring in the QTP, which has not been reported before.…”
Section: Discussioncontrasting
confidence: 47%
See 2 more Smart Citations
“…In an alternative scenario, plants in the QTP show high genetic diversity and ancestral haplotypes, which suggest an in situ survival during the LGM on the plateau [13], [18]. Nevertheless, our study reveals a distinct phylogeographical history of plants occurring in the QTP, which has not been reported before.…”
Section: Discussioncontrasting
confidence: 47%
“…However, our knowledge of phylogeographical histories of organisms occurring in the QTP and HHM as well as causal correlations with climatic fluctuations has been limited so far, due to finite phylogeographical studies in the QTP and its adjacent areas in particular for plants [8][18]. Interestingly, these studies suggest remarkable differences in the phylogeographical history of the species involved, although two main patterns might be inferred.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies suggested refugia in the Hengduan Mountains on the eastern border of the QTP (Zhang et al, 2010; Wang et al, 2011b). It has been suggested that advances of the Tibetan glaciers were less prominent than other regions in the Northern Hemisphere, likely due to arid conditions and complex topography, and potential habitats for cold-tolerant species could be found in the plateau and served as refugia in the interior Central regions of the QTP during interglacial periods in the Quaternary (Schäfer et al, 2002; Wang et al, 2009a,2011b; Shimono et al, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…In China, P. fruticosa also called “Jinlaomei” and “Gesanghua”, its altitude ranges from 400 to 5000 m [13]. Apart from its common gardening applications, it also has numerous medicinal virtues [14].…”
Section: Introductionmentioning
confidence: 99%